Risk Factors of Syphilis and HIV/AIDS Coinfection - Yuindartanto, Andre; Hidayati, Afif Nurul; Indramaya, Diah Mira; Listiawan, M. Yulianto; Ervianti, Evy; Damayanti, Damayanti (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Syphilis infection and HIV are major health problems worldwide. Both of these diseases can be transmitted through sexual contact, so often a person suffers from both diseases at the same time. Purpose: To describe the risk factors of syphilis and HIV/AIDS coinfection in the Infectious Disease Intermediate Treatment Unit (UPIPI) inpatient and outpatient ward of Dr. Soetomo General Academic Hospital in 2019. Methods: The study design used in this study is a retrospective descriptive study aimed at evaluating sexual and non-sexual factors that cause syphilis and HIV coinfection. The research population was patients in the inpatient and outpatient rooms of UPIPI RSUD Dr. Soetomo Surabaya for the January-December 2019 period. The sampling technique was sourced from secondary data, namely medical record data from the inpatient and outpatient rooms of UPIPI RSUD Dr. Soetomo Surabaya for the period January-December 2019. The data in this study were obtained from medical records and patient biodata. Result: Based on the calculation results, it is known that age group (P=0.022>0.05), and gender (P=0.024>0.05) had no effect on the risk of syphilis and HIV coinfection, while marital status (P=0.048<0.05), sexual orientation (P=0.048<0.05), transmission model (P=0.044<0.05), and type of work (P=0.046<0.05fected the risk of syphilis and HIV coinfection. Conclusion: People with HIV/AIDS are expected to be active in participating in programs that are needed by patients, such as antiretroviral (ARV) therapy assistance programs and counseling that will prolong the quality of life in various aspects of life, both physical, psychological and social aspects.